Identification of a Novel Mutation in TNFAIP3 in a Family With Poly-Autoimmunity - Rossi, Marianna Nicoletta; Federici, Silvia; Uva, Andrea; Passarelli, Chiara; Celani, Camilla; Caiello, Ivan; Matteo, Valentina; Petrocchi, Stefano; Mortari, Eva Piano; De Benedetti, Fabrizio; Prencipe, Giusi; Insalaco, Antonella (Frontiers in Immunology, 2022)
Haploinsufficiency of A20 (HA20) is an inflammatory disease caused by mutations in the TNFAIP3 gene typically presenting with Behcet’s-like disease. A20 acts as an inhibitor of inflammation through its effect on NF-kB pathway. Here we describe four consanguineous patients (three sisters and their mother) with a predominantly autoimmune phenotype, including thyroiditis, type I diabetes, hemolytic anemia and chronic polyarthritis. All patients had recurrent oral ulcers, with only 1 patient presenting also recurrent fever episodes, as a classical autoinflammatory feature. Next generation sequencing identified a novel heterozygous frameshift mutation (p.His577Alafs*95) that causes a premature stop codon in the zinc finger domain of A20, leading to a putative haploinsufficiency of the protein. Functional analyses confirmed the pathogenicity of the mutation. The variant was associated with decreased levels of A20 in blood cells. Accordingly, ex-vivo LPS-stimulated patients’ peripheral blood mononuclear cells (PBMCs) showed higher levels of NF-kB phosphorylation, as well as increased production of the proinflammatory cytokines IL-1β, IL-6 and TNF-α. Moreover, in agreement with observations in mice models, demonstrating a role for A20 in inhibiting STAT1 and IFNg pathways, markedly higher circulating levels of the two IFNg-inducible chemokines CXCL9 and CXCL10 were detected in all patients. Supporting the findings of a hyperactivation of IFNγ signaling pathway in HA20 patients, patients’ monocytes showed higher levels of STAT1 without stimulation, as well as of higher phosphorylated (active) STAT1 following IFNγ-stimulation. In conclusion, our study show that in the clinical spectrum of HA20 autoimmune features may predominate over autoinflammatory features and demonstrate, from a molecular point of view, the involvement of A20 in modulating not only the NF-kB, but also the IFNγ pathway.